Cancer incidence and mortality in China, 2015 - Siwei Zhang (Elsevier, 2021)
Background: National Cancer Center (NCC) updated nationwide cancer statistics using population-based cancer registry data in 2015. Methods: 501 cancer registries submitted data, among which 368 registries with high quality data were included in analysis. Numbers of nationwide new cancer cases and deaths were estimated using incidence and mortality rates and corresponding national population stratified by area, sex, age group and cancer site. The world Segi's population was applied for the calculation of age-standardized rates. Results: About 3,929,000 new cancer cases were diagnosed. The crude incidence rate was 285.83/100,000 and the age-standardized incidence rate by world standard population (ASIRW) was 186.39/100,000. ASIRW was higher in urban areas than in rural areas. South China had the highest ASIRW while Southwest China had the lowest ASIRW. Age-specific incidence rate was higher in males for population younger than 20 years or over 49 years. From 2000 to 2015, the ASIRWs for esophageal cancer, gastric cancer and liver cancer decreased significantly. The ASIRWs for colorectal cancer in whole population and for lung cancer, breast cancer, cervix cancer, uterus cancer and thyroid cancer in females increased significantly. 2,338,000 cancer deaths were reported. The crude mortality rate was 170.05/100,000 and the age standardized mortality rate by world standard population (ASMRW) was 105.84/100,000. ASMRW was higher in rural areas than in urban areas. Central China had the highest ASMRW while North China had the lowest ASMRW. Age-specific mortality rates in males were higher than that in females in every age group. From 2000 to 2015, the ASMRWs for esophageal cancer, gastric cancer, liver cancer and lung cancer decreased significantly. The ASMRWs for colorectal cancer, pancreas cancer and prostate cancer in males and for breast cancer, cervix cancer and thyroid cancer in females increased significantly. Conclusions: Cancer has become a major life-threatening disease in China. Disease burdens differed across areas. Disease burdens for esophageal cancer, gastric cancer and liver cancer have decreased, while disease burdens for colorectal cancer, female breast cancer, cervix cancer and thyroid cancer have increased over the last 15 years. National and regional initiative for cancer prevention and control should be prioritized.